2021
DOI: 10.1021/acssuschemeng.1c02597
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon-Supported Ruthenium as a Catalyst for the Solvent- and Initiator-Free Aerobic Epoxidation of Limonene

Abstract: The activity and selectivity of ruthenium catalysts supported on various activated carbons have been investigated in the epoxidation of limonene using molecular oxygen, the greenest oxidizing agent, under solvent/reductant- and initiator-free reaction conditions. The catalysts were prepared via different methods including impregnation, sol immobilization, and cation exchange. Supported Ru catalysts with a metal particle size ranging from 1.8 to 21 nm were obtained. The catalyst prepared by cation exchange usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…[9][10][11][12][13][14] Nowadays, the development of efficient heterogenized catalytic systems for the epoxidation of olefins remains a challenge. 4,[15][16][17] Different types of porous materials, such as zeolites, 18 polymers, 19 mesoporous silicas, 14 activated carbons 20 or MOFs, 21 have been employed as supports of transition metal complexes for liquid phase epoxidation of olefins.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Nowadays, the development of efficient heterogenized catalytic systems for the epoxidation of olefins remains a challenge. 4,[15][16][17] Different types of porous materials, such as zeolites, 18 polymers, 19 mesoporous silicas, 14 activated carbons 20 or MOFs, 21 have been employed as supports of transition metal complexes for liquid phase epoxidation of olefins.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the pronounced alteration of D-Limonene caused by its degradation through free radical reactions in the ultraviolet range. 28 Additionally, the amino group (−NH 2 ) in the chitosan backbone creates cationic functional sites in the OCNF, increasing the adsorption of UV protection. As a result, the exceptional UV-blocking properties of the resultant films will significantly expand their potential applications in the field of UV protection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, as d -Limonene contents increase gradually, impressive UV-blocking abilities of the films (CFL-1, CFL-2, CFL-3, and CFL-4) against UVB with blocking rates as high as 90.8%, 96.5%, 98.6%, and 98.5%, and UVA radiation at the rates of 50.0%, 50.1%, 69.3%, and 66.9%, respectively, are ultimately achieved, indicating that the d -Limonene has a positive effect on UV-blocking. This is primarily due to the pronounced alteration of d -Limonene caused by its degradation through free radical reactions in the ultraviolet range . Additionally, the amino group (−NH 2 ) in the chitosan backbone creates cationic functional sites in the OCNF, increasing the adsorption of UV protection.…”
Section: Resultsmentioning
confidence: 99%
“…A study investigated the direct epoxidation of limonene using highly dispersed ruthenium (Ru) supported on activated carbon (AC) prepared by several immobilisation techniques, without the use of solvents. 52 The study found that in mild reaction conditions, Ru/AC showed excellent efficacy in the solvent-free epoxidation of limonene. Furthermore, the selectivity of the catalyst towards epoxidation was significantly impacted by the method of catalyst preparation.…”
Section: Epoxidation Of Terpenesmentioning
confidence: 96%